Síntese e caracterização de vidro bioativo contendo íons cério e cobalto com ação antimicrobiana e antioxidante conjugado com hidrogel bicamada de PVA/PAA para potencial tratamento de lesões cutâneas - Ingrid Elen Pinto e Souza (2023)
The formation of chronic wounds is a public health concern due to the high number of cases and complex interactions between the skin and underlying tissues. Tissue engineering is a field that seeks materials to aid in the restoration and progression of tissue healing. For example, smart bioactive dressings capable of promoting wound healing in an organized, rapid, effective, and bioactive manner are being explored. Bioactive glass (BG) is a material that stimulates collagen formation in soft tissues through the release of ions present in its structure. Its composition can be modified by incorporating different ions with therapeutic functions, such as cerium (Ce) for antioxidant action and cobalt (Co) for antimicrobial activity. BG is commonly used in the development of dressings when combined with polymeric materials, especially those responsive to physiological conditions, such as pH. This study aimed to develop new compositions of BG nanoparticles incorporating Ce and Co ions through the sol-gel route with ion impregnation after silica synthesis. The materials were characterized using microscopy, chemical analysis, and structural analysis techniques. Results indicate successful incorporation of these ions into the BG structure as modifiers and network formers. The BGs exhibited spherical morphology, mesoporosity, and nanoscale size. Antioxidant, antimicrobial activity, and biocompatibility of the BGs were confirmed. Subsequently, BG was incorporated into a double-layer hydrogel system of poly(vinyl alcohol) and poly(acrylic acid) (PVA-PAA) to create dressings with high absorption capacity. Under basic pH conditions (infected wound), the nanocomposites demonstrated controlled release of therapeutic ions and higher absorption capacity for simulated wound exudate compared to market products. Additionally, they exhibited good fluid movement and water vapor transmission. In vitro biological assays indicated cellular compatibility for all developed compositions, and higher concentrations of BG in the nanocomposite resulted in increased antibacterial activity. The nanocomposite was responsive to the pH of the environment, demonstrating the ability to identify and appropriately treat chronic injuries, thereby accelerating the healing process. Therefore, the proposed application of the employed BGs in PVA/PAA double-layer dressings shows potential for restoring cutaneous tissues due to their intelligent and pH-responsive control, allowing for the release of therapeutic ions.